The experiences of adults with learning disabilities in the UK during the COVID-19 pandemic: qualitative results from Wave 1 of the Coronavirus and people with learning disabilities study. Issue 4 (27th October 2021) - Flynn, Samantha; Caton, Sue; Gillooly, Amanda; Bradshaw, Jill; Hastings, Richard P.; Hatton, Chris; Jahoda, Andrew; Mulhall, Peter; Todd, Stuart; Beyer, Stephen; Taggart, Laurence; ,
Abstract : Purpose: The purpose of this paper is to present data about the experiences of adults with learning disabilities during the COVID-19 pandemic across the UK. Design/methodology/approach: Interviews were conducted with 609 adults with learning disabilities. Family carers and support staff of another 351 adults with learning disabilities completed a proxy online survey. The data were collected between December 2020 and February 2021 and concerned both worries/negatives and anything positive that had happened because of the COVID-19 pandemic. Findings: Social isolation was the most commonly reported worry/negative for adults with learning disabilities, with other frequently reported worries/negatives including: changes to/loss of routine; loss of support/services; and decreased health/well-being/fitness. A large proportion of participants indicated that nothing positive had happened because of COVID-19, but some positives were reported, including: digital inclusion; more time spent with important people; improved health/well-being/fitness; and, a slower pace of life. Practical implications: Future pandemic planning must ensure that adults with learning disabilities are supported to maintain social contact with the people who matter to them and to support their health and well-being (including maintaining access to essential services and activities). Some adults with learning disabilities may benefit from additional support to improve their digital confidence and access. This may in turn enable them to maintain contact with family, friends and support services/activities. Originality/value: This is the largest study about the experiences of adults with learning disabilities during the COVID-19 pandemic in the UK. The authors primarily collected data directly from adults with learning disabilities and worked with partner organisations of people with learning disabilities throughout the study.